Same old, same old: from boring to creative presentation - Conlan, Chris; Ahmed, Sabreena (BRAC University, 2012)
This study compares attitudes of tertiary-level students in Australia and Bangladesh towards the use of technology in lectures and seminars. Students were shown audiovisual recordings of two seminars. The content and teacher in both seminars were identical. One seminar, however, used a PowerPoint presentation package while the other used usual whiteboard–marker pen, and post-it notes as additional tools for the presentation. Findings from the research suggest that both Australian and Bangladeshi students preferred the audiovisual recording without PowerPoint as it was more effective and interactive to them. These findings have important implications with respect to educational planning and effectiveness of modern technology in making presentations in both of these countries.